PENGARUH CAMPURAN ETANOL DENGAN BAHAN BAKAR PERTAMAX TERHADAP PERFORMA MESIN MOTOR YAMAHA JUPITER Z1 TAHUN 2014 - Fikri Ulul Albab; Agus Adi Nursalim; Engkus Kusmadi Wijaya (Universitas Islam Al-Ihya Kuningan, 2023)
The development of technology in the automotive world, especially motorcycles, is growing rapidly and its use is increasing every year. There are many ways to improve engine performance, including in the ignition and fuel sectors. In the fuel sector, the use of high-octane fuels, including Pertamax, is needed to compensate for high compression pressures. To further improve engine performance, one alternative is to mix ethanol in Pertamax fuel. This research uses experimental method with quantitative research type. The tool used to perform the test is a dyno test. The independent variables used in this research are pure pertamax, 20% ethanol mixture and 80% Pertamax, 30% ethanol mixture and 70% Pertamax. The dependent variables in this study are torque and power. The results showed that there was an effect of adding ethanol to the engine performance of the Yamaha Jupiter Z1 which included torque and power. In general, complete combustion occurs with a high octane rating of the fuel to compensate for the high compression pressure.